The effects of plyometric conditioning on post-activation bench press performance - Krzysztofik, M.; Wilk, M. (Journal of Human Kinetics, 2020)
The present study aimed to determine the effects of plyometric push-ups as a conditioning activity (CA) on high-loaded bench press performance. Two groups of resistance-trained males age (24.5 ± 2.6 years, body mass 84.8 ± 8 kg) performed one of two CA protocols: 3 sets of 5 repetitions of plyometric push-ups with a 1 min rest interval between sets (PAPE; n=12) or equal time aerobic warm-up (CONT; n=12). Four minutes after completion of the CA protocols the participants performed 3 sets of 3 repetitions of the bench press exercise at 70%1RM and 4 min rest interval between sets to assess post-activation differences in peak power output (PP), mean power output (MP), peak bar velocity (PV), and mean bar velocity (MV) between conditions. The two-way ANOVA revealed significant condition × set interaction effect for PP (p<0.01), MP (p<0.05), PV (p<0.01), and MV (p=0.02). The post hoc for condition × set interaction showed that PAPE caused a significant decrease in PP and PV for P-Set2 and P-Set3 when compared to baseline (BA). The MP and MV for the PAPE condition decreased significantly during the P-Set3 compared to BA and to P-Set1. The t-test comparisons for delta values showed significant differences between PAPE and CONT in PP for P-Set1 - BA (p<0.01), in MP for P-Set2 - P-Set1 (p<0.03) and for P-Set3 - P-Set1 (p=0.04). Furthermore, there were significant differences in PV for P-Set3 - BA; P-Set2 - P-Set1; P-Set3 - P-Set1 (p<0.01; p<0.01; p<0.02 respectively). Finally, there were significant differences in MV for P-Set1 - BA; P-Set2 - P-Set1 and P-Set3 - P-Set1 (p<0.01; p<0.01; p<0.02 respectively). This study demonstrated that plyometric push-ups lead to performance enhancement of the bench press exercise at 70%1RM. The increases in performance were observed only in the first set following the CA, while a significant decrease of these variables was registered in P-Set2 and P-Set3.